Neonatal Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The clinical patterns, etiologies and times of onset of seizures were determined in a retrospective study of 150 newborns with seizures evaluated between 1982-87 in the neonatal intensive care unit at Washington University School of Medicine, Children's Hospital, St. Louis, MO.